ANALISIS PENGARUH UMPAN BALIK SUPERVISI TERHADAP KINERJA - Ngatno, Ngatno (JURNAL ILMU SOSIAL, 2006)
Sales force was the company's main function that were directly related to consumer. Since then, they can verbally influence the consumer to decide or execute buying behaviour. Performance of sales force was mostly influenced by some factors, both the sales person indi-vidually and outsides of sales persons individual. One of factors that can influence sales force performance as feedback factor of supervision. This research used causal research type with primary data at most and secondary data as supporting. The sampling method was census, besides data was collected with polling method (structural questionnaire). It's analysis and hypothesis testing tools were The Structural Equation Modelling (SEM) of AMOS statistic software. Analysis factors (confirmatory factor analyse) reveals that the three indicators being suggested to measure output feedback construct, behaviour feedback, and sales performance, can be accepted, since its regression weight is greater than 0.40 or having probability less than 0.05. Correlation between output feedback and sales performance is 0.22, correlation between behaviour feedback and sales performance is 0.34. The analysis to evaluate normality data reveal that data being collected was normal, that the assessment of normality is 1.282, besides its critical ratio at significance level 1% is Â±2.58. the analysis shows that determinant rate of covariant matrix 0.055. The direct impact of variables shows that the direct impact of behaviour feedback to performance 0.481, besides the direct impact of output feedback to sales performance is -0.626.